High Exploration Behavior of Termite Propagules Can Enhance Invasiveness - Pailler, Louis; Matte, Arthur; Groseiller, Alexis; Eyer, Pierre-André; Ruhland, Fanny; Lucas, Christophe (Frontiers in Ecology and Evolution, 2022)
Social life is usually associated with enhanced propagule pressure, which increases the chance of introducing several individuals during a single introduction event. Social insects are therefore among the most successful invasive species, benefiting from rapid establishment and increased foundation success in new habitats. In termites, propagule pressure may also be increased by the development of reproductive individuals from a small group of foraging workers. This suggests that enhanced exploration activity may increase propagule pressure through an elevated chance of transporting isolated groups of foragers. Here, we analyzed the exploration behavior of three termite species of the Reticulitermes genus, comparing the invasive species R. flavipes (testing both native and introduced populations) to the native species R. grassei and R. lucifugus. Different features representative of the exploration capacity were measured during 48h, including: the number of tunnels, the length of tunnels, the number of foragers, and the interindividual distance of foragers in a straight line or through tunnels. Our results show that compared to the native Reticulitermes species, R. flavipes foragers from both populations dug more tunnels with a longer total length, and individuals were more spatially dispersed and covered a larger exploration zone. These findings suggest that the enhanced exploration ability of R. flavipes may have played a role in its invasion success, by increasing its propagule pressure through a higher chance of human-mediated transport. In addition, the absence of differences between the native and introduced populations of R. flavipes suggests that the exploration behaviors facilitating the worldwide invasion of this species originated in its native range.